From Capture to Sale The Portuguese Slave Trade to Spanish South America in the Early Seventeenth Century - Newson, Linda A. (The Atlantic World, 2007)
Based on exceptionally rich private papers of Portuguese slave traders, this study provides unique insight into the diet, health and medical care of slaves during their journey from Africa to Peru in the early seventeenth century.; Readership: All those interested in the history of the slave trade and slavery in both Africa and Spanish America, as well as the history of food and medicine in the early modern period.